2021
DOI: 10.3389/fcvm.2021.679105
|View full text |Cite
|
Sign up to set email alerts
|

Energy Drink-Associated Electrophysiological and Ischemic Abnormalities: A Narrative Review

Abstract: An increasing number of cardiovascular adverse effects, emergency room visits, and deaths have been linked to energy drinks. In this review, we summarized available published literature assessing electrophysiological and ischemic adverse effects associated with energy drink consumption. Overall, 32 case reports and 19 clinical trials are included in this review. Ventricular arrhythmia, supraventricular arrhythmia, and myocardial ischemia were amongst the most commonly reported in case reports with 3 having a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…In addition, 12% percent of adolescent ED consumers drink at least 1.065 liters of ED in one setting and are therefore identified as “high acute” consumers ( 1 ). The high prevalence of chronic and excessive ED consumers among children and teenagers is alarming: While the chronic ED consumption increases the risk of arterial hypertension, glucose metabolism disorders and overweight, the excessive ED consumption, predominantly in combination with drugs, is associated with rhythm disorders ( 2 ). Interestingly, a recent study of our department revealed a significantly increased number of supraventricular extrasystoles after acute ED consumption (3 mg caffeine per kilogram of bodyweight) in 26 healthy children and teenagers ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, 12% percent of adolescent ED consumers drink at least 1.065 liters of ED in one setting and are therefore identified as “high acute” consumers ( 1 ). The high prevalence of chronic and excessive ED consumers among children and teenagers is alarming: While the chronic ED consumption increases the risk of arterial hypertension, glucose metabolism disorders and overweight, the excessive ED consumption, predominantly in combination with drugs, is associated with rhythm disorders ( 2 ). Interestingly, a recent study of our department revealed a significantly increased number of supraventricular extrasystoles after acute ED consumption (3 mg caffeine per kilogram of bodyweight) in 26 healthy children and teenagers ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…In correlation with their popularity, reports of emergency department visits linked to ED consumption are rising: The excessive consumption of EDs, especially in combination with party drugs or in the presence of a cardiac condition, is associated with adverse cardiovascular events (e.g. ventricular arrhythmia, supraventricular arrhythmia, myocardial ischemia) ( 2 ). Interestingly, a significantly prolonged QTc interval in adult study subjects was demonstrated in several clinical trials after ED consumption ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, a narrative review assessing the effect of energy drinking on electrophysiology and ischemic abnormalities from 2001 to 2019 was published in 2021. The review described 28 published case reports; arrhythmia was described in 20 cases and only one case of WPW [18]. This case of WPW was a 34-year-old male who presented to the EDs with tachycardia and chest pain after consumption of an energy drink.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive intake, particularly combined with party drugs and alcohol and/or in the presence of cardiovascular conditions, may more frequently lead to adverse cardiovascular events such as cardiac arrhythmia, myocardial ischemia, etc. [4]. Several clinical trials demonstrated a significant increase of arterial blood pressure after acute ED consumption in adult subjects [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%